ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT PEMBANGUNAN JAYA ANCOL Tbk TAHUN 2016-2020 - Israr, Dyna Aulia; Zaharman, Zaharman; Novianti, Serly (Komunitas Manajemen Kompetitif, 2024)
The research was conducted at PT Pembangunan Jaya Ancol Tbk which is a company that is included in the tourism and recreation industry listed on the Indonesia Stock Exchange. The purpose of this study is to assess and analyze the financial performance of PT Pembangunan Jaya Ancol Tbk from 2016 to 2020 using financial ratio analysis. The financial ratio used is the liquidity ratio consisting of the current ratio, the fast ratio and the cash ratio. The solvency ratio consists of the debt to asset ratio, debt to equity ratio, and long-term debt to equity ratio. The activity ratio consists of the turnover of fixed assets and the turnover of total assets. The profitability ratio consists of net profit margin, return on investment, and return on equity. The growth ratio consists of sales growth and profit growth. The data used in this study is the financial report data of PT Pembangunan Jaya Ancol Tbk from 2016 to 2020. The results of this study show the financial performance of PT Pembangunan Jaya Ancol Tbk in 2016-2020 as measured by the ratio of liquidity, solvency, activity, profitability in a bad state and the growth ratio has increased and decreased. From this financial ratio analysis, it can be seen that the financial performance of PT Pembangunan Jaya Ancol Tbk is not good because the company's average ratio is below the industry average. Keywords: Financial Ratio Analysis, Liquidity Ratio, Solvency Ratio, Activity Ratio, Profitability Ratio, and Growth Ratio